Identifikasi dan Karakterisasi Bakteri Asam Laktat dari Bekasam Ikan Gabus (Channa striata) Berdasarkan Pewarnaan Gram dan Morfologi Koloni - Salsabila Rahman; Ardi Mustakim (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Bekasam is a traditional Indonesian fermented food produced through spontaneous fermentation involving microorganisms, particularly lactic acid bacteria (LAB). LAB plays a crucial role in the fermentation process by producing lactic acid, which lowers pH, inhibits pathogenic microbial growth, and enhances flavor and food safety. This study aimed to identify and characterize LAB isolated from fermented snakehead fish (Channa striata) based on Gram staining and colony morphology. The research began with bacterial isolation using NA Nutrient Agar, followed by macroscopic observation of colony characteristics including shape, edge, elevation, color, and size. Subsequently, Gram staining was performed to determine the cell wall structure and microscopic morphology of the bacteria. The results showed that the bacterial isolates from bekasam generally had circular colonies, white to cream in color, smooth surface, and were Gram-positive rod-shaped cells. In conclusion, bekasam from snakehead fish contains dominant lactic acid bacteria with distinctive colony morphology and Gram-positive characteristics, indicating potential as a natural starter culture for food fermentation.